Anodal tDCS and High-Frequency tRNS Targeting the Occipitotemporal Cortex Do Not Always Enhance Face Perception - Willis, Megan L.; Costantino, Andrea I.; Nitsche, Michael. A.; Palermo, Romina; Rivolta, Davide (Frontiers in Neuroscience, 2019)
There has been increasing interest in the utility of transcranial electrical stimulation as a tool to enhance cognitive abilities. In the domain of face perception, enhancements have been reported for both transcranial direct current stimulation (tDCS) and high-frequency transcranial random noise stimulation (tRNS) targeting the occipitotemporal cortex. In a series of two experiments, we attempted to replicate these findings for face identity perception, and extend on previous studies, to determine if similar enhancements are also observed for object and facial expression perception. In Experiment 1, using a single blind, between-subjects design in healthy volunteers (N = 53), we examined whether anodal tDCS over the occipitotemporal cortex enhanced performance on tasks involving perception of face identity, facial expression, and object stimuli, when compared to sham stimulation. We failed to replicate previous findings of enhanced performance on face and object perception, nor extend findings to facial expression perception. We did however find preliminary evidence that anodal tDCS increased accuracy across the three tasks for non-Caucasians, when participant race (i.e., Caucasian, non-Caucasian) was included as a between-subjects factor in an exploratory analysis. No such pattern was evident for Caucasian participants. In Experiment 2, using a single blind, between-subjects design (N = 39), we examined the effect of high-frequency tRNS over the occipitotemporal cortex using the same three tasks employed in Experiment 1. We failed to replicate previous findings of enhanced face perception following high-frequency tRNS over the occipitotemporal cortex, relative to sham stimulation, and similarly, found no evidence of enhanced facial expression and object perception. In contrast to Experiment 1, participant race did not appear to moderate the effect of high-frequency tRNS. The findings of the current study highlight the impact of individual traits, in this case race, or perceptual history, on the modulatory effect of anodal tDCS on face perception, and hint for different efficacy of, on first sight, related stimulation protocols. Future studies should explore the foundation of these differential effects in greater detail. Moreover, these findings again stress the dependency of neuromodulatory intervention effects on individual characteristics.